Terminological collocations in different types of medical discourse - Lyamova, Oksana O. (Sovremennye issledovaniia sot͡s︡ialʹnykh problem, 2025)
Background. Every language is full of collocations. It is almost impossible to speak without collocations because the meaning of any word is determined and specified by the company it keeps. Collocations are widely used in all spheres of life and various types of professional discourse. Medical discourse is a special linguistic subsystem designed for professional communication, where a doctor acts as the communicative leader. Terminological collocations are actively used in authentic medical texts, publications, and doctor-patient communication. We should always keep in mind that the general meaning of such combinations is not equal to the meaning of each component, they cannot always be translated word by word, that`s why correct translation and use of terminological collocations is extremely important while working with medical information. Purpose – to analyze the lexical content of well-known courses of medical English, authentic dictionaries and textbooks on medicine to identify and classify the main models of terminological collocations in different types of medical discourse. Materials and methods. Contemporary courses of medical English: «Check Your English Vocabulary for Medicine» (A&C Black); «Medicine 1 / 2» (S. McCarter); «Nursing 1 / 2» (T. Grice); «Professional English in Use: Medical» (E.H. Glendinning); «Test Your Professional English: Medical» (A. Pohl); some medical dictionaries (London Dictionary of Medical Terms, Dictionary of Nursing, Illustrated Medical Dictionary) and textbooks on general and clinical medicine: Anatomy and Physiology for Health Professionals (J. Moini); Eyewitness. Human Body (R. Walker); How it Works Book of the Human Body (Imagine Publishing Ltd); The Facts on File Illustrated Guide to the Human Body (The Diagram Group), Harrison`s Pulmonary and Critical Care Medicine (McGraw-Hill Education), Williams Textbook of Endocrinology (S. Melmed et al.), Nadas' Pediatric Cardiology (Elsevier Inc.), Shaw’s Textbook of Gynaecology (V.G. Padubidri, S.N. Daftary), Adams and Victor’s Principles of Neurology (A.H. Ropper et al.), Pediatric Otolaryngology. Principles and Practice Pathways (R.F. Wetmore, H.R. Muntz, T.J. McGill), etc. Results. Analysis of the lexical content shows that each type of medical discourse is attributed by the following semantic groups of terminological collocations: collocations describing the structure and work of the human body ("anatomy and physiology"); word combinations naming the most common symptoms and signs of different diseases ("signs and symptoms"); collocations naming diseases and conditions of various organs and systems («diseases and conditions»); combinations describing medical personnel, instruments, medicines, technologies used in diagnosis and treatment ("diagnosis and treatment"). A special group includes terminological collocations, which are considered to be proper names. The article presents different examples of the most common terminological collocations used in various types of medical discourse (cardiology, pulmonology, gastroenterology, neurology, endocrinology). Обоснование. Устная и письменная речь любого языка насыщена коллокациями. Без коллокаций практически невозможно изъясняться в большинстве языков мира, т.к. значение любого слова определяется и конкретизируется именно в его окружении. Коллокации широко применяются во всех сферах жизни и различных видах профессионального дискурса. Медицинский дискурс представляет собой особую языковую подсистему, предназначенную для профессиональной коммуникации, в которой врач выступает безусловным коммуникативным лидером. Терминологические коллокации активно используются в аутентичных медицинских текстах, пабликах, общении врача и пациента. Необходимо помнить, что значение таких сочетаний не равно сумме значений каждого из их компонентов, при переводе они не всегда могут передаваться пословно, поэтому грамотный перевод терминологических коллокаций крайне важен для работы с медицинской информацией. Цель исследования – анализ лексического контента общеизвестных курсов медицинского английского, аутентичных словарей и учебников по медицине на предмет выявления и классификации основных моделей терминологических коллокаций в разных видах медицинского дискурса. Материалы и методы. Учебные курсы медицинского английского: «Check Your English Vocabulary for Medicine» (A&C Black); «Medicine 1 / 2» (S. McCarter); «Nursing 1 / 2» (T. Grice); «Professional English in Use: Medical» (E.H. Glendinning); «Test Your Professional English: Medical» (A. Pohl); ряд толковых медицинских словарей (London Dictionary of Medical Terms, Dictionary of Nursing, Illustrated Medical Dictionary) и учебников по общей и клинической медицине: Anatomy and Physiology for Health Professionals (J. Moini); Eyewitness. Human Body (R. Walker); How it Works Book of the Human Body (Imagine Publishing Ltd); The Facts on File Illustrated Guide to the Human Body (The Diagram Group), Harrison`s Pulmonary and Critical Care Medicine (McGraw-Hill Education), Williams Textbook of Endocrinology (S. Melmed et al.), Nadas' Pediatric Cardiology (Elsevier Inc.), Shaw’s Textbook of Gynaecology (V.G. Padubidri, S.N. Daftary), Adams and Victor’s Principles of Neurology (A.H. Ropper et al.), Pediatric Otolaryngology. Principles and Practice Pathways (R.F. Wetmore, H.R. Muntz, T.J. McGill), etc. Результаты. Анализ лексического контента показал, что в каждом виде медицинского дискурса наиболее частотными оказались следующие семантические группы коллокационных терминологических словосочетаний: коллокации, описывающие строение и работу человеческого организма («anatomy and physiology»); устойчивые словосочетания, называющие наиболее распространенные симптомы и признаки заболеваний («signs and symptoms»); коллокации, дающие название заболеваниям и состояниям различных органов и систем («diseases and conditions»); сочетания, описывающие медицинский персонал, инструментарий, лекарственные препараты, технологии, используемые в диагностике и лечении и т.д. («diagnosis and treatment»). В особую группу выделяются терминологические коллокации, которые являются именами собственными (proper names). В статье приводятся примеры наиболее распространенных коллокационных словосочетаний, используемых в разных видах медицинского дискурса (cardiology, pulmonology, gastroenterology, neurology, endocrinology).